2000
DOI: 10.1007/s002440010078
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bioaccumulated Selenium on Mortalities and Deformities in the Eggs, Larvae, and Fry of a Wild Population of Cutthroat Trout ( Oncorhynchus clarki lewisi )

Abstract: To determine if elevated concentrations of waterborne selenium (Se), caused by coal mining, in the Elk River in southeastern British Columbia, may be causing reproductive or teratogenic effects in wild cutthroat trout (Oncorhynchus clarki lewisi), fertilized eggs from exposed and reference fish were raised in the laboratory. Eggs from each female were reared separately and the percent mortalities and deformities were related to the selenium content of the eggs. Selenium concentrations in females from the expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 29 publications
6
64
1
Order By: Relevance
“…Selenium has been documented to have toxic effects on aquatic life (Lemly 1993). In fact, mortality of rainbow trout, chinook salmon, striped bass, and bluegill has been documented at concentrations of selenium ranging from 4 to 10 µg/L (Kennedy et al 2000). As such, we grouped the Mud River sites according to presence (n=5) or absence (n=3) of selenium and repeated the analysis of total number of species and total number of benthic species (Fig.…”
Section: Evaluation Of Effects Of Miningmentioning
confidence: 99%
“…Selenium has been documented to have toxic effects on aquatic life (Lemly 1993). In fact, mortality of rainbow trout, chinook salmon, striped bass, and bluegill has been documented at concentrations of selenium ranging from 4 to 10 µg/L (Kennedy et al 2000). As such, we grouped the Mud River sites according to presence (n=5) or absence (n=3) of selenium and repeated the analysis of total number of species and total number of benthic species (Fig.…”
Section: Evaluation Of Effects Of Miningmentioning
confidence: 99%
“…In addition, Orr et al (2005) have recently shown that biota in coal mine-affected lentic systems accumulated more selenium than those in coal mine-affected lotic systems. However, contrasting with these results and fueling concern about potential effects of coal mining on selenium mobilization and bioaccumulation, are studies that reported increased levels of selenium in fish at sites downstream from coal mines in the Rocky Mountains of Canada (Kennedy et al, 2000;Palace et al, 2004;Holm et al, 2005). One of those studies reported a significant, selenium-dependent increase in deformities in trout fry hatched from fertilized eggs of fish from coal mine-affected streams (Holm et al, 2005), heightening to an even greater extent the level of concern about possible coal mining effects.…”
Section: Introductionmentioning
confidence: 74%
“…A recent paper by Kennedy et al (2000) examined the potential e!ects of selenium in a lotic environment by comparing mortalities and deformities in the progeny of cutthroat trout (Oncorhynchus clarki) collected from a selenium-laden river impacted by coal mining. A nearby lake in British Columbia, Canada, was used as the reference site.…”
Section: Critique Of Lotic Investigationmentioning
confidence: 99%